Editorial: Comics and Transnational Exchanges. Issue 1 (1st June 2019) - ,
Abstract : The title of our journal implies there is such a thing as European comic art, even if in practice it is intended to indicate we focus on work produced (outside the United States) in European languages, leaving the fields of South East Asian and US comics to other publications in the discipline. However, European comics clearly have not developed in isolation from other comics traditions: from the earliest days, they have both impacted and absorbed influences from elsewhere: to cite an obvious example, Rudolph Dirks's Katzenjammer Kids was modelled on Wilhelm Busch's Max und Moritz, and both have served as templates for generations of mischievous children from Alain Saint-Ogan's Zig et Puce, through Dennis the Menace, in both US and UK incarnations.